Assessing the Challenges and Benefits of Electric Truck Adoption in Truck Logistics: A Case Study of Truck Logistics Companies in Indonesia - Otari Akenzi (Eduvest - Journal of Universal Studies, 2026)
This study examines the challenges and benefits of electric truck adoption in Indonesia’s truck logistics sector through a case study of PT Seino Indomobil Logistics. Employing a qualitative research approach, data were collected through semi-structured interviews with senior management, including the Chief Operating Officer, Chief Financial Officer, Head of Field Operations, and Head of Vehicle Management. The analysis utilized the Technology-Organization-Environment (TOE) framework, complemented by PESTEL and SWOT analyses, to provide a comprehensive understanding of adoption dynamics. The findings reveal that electric trucks offer substantial benefits, including reduced operational costs through lower fuel and maintenance expenses, enhanced environmental sustainability, improved customer value for ESG-committed clients, and greater operational predictability. However, adoption is constrained by critical challenges: limited charging infrastructure, high upfront capital costs, operational complexity in fleet integration, technical uncertainties regarding battery lifecycle, and an unsupportive policy environment characterized by diesel fuel subsidies and minimal incentives for electric vehicles. The study demonstrates that successful adoption requires strategic alignment across technological readiness, organizational capabilities, and external environmental conditions. Recommendations include implementing phased pilot projects on suitable routes, developing depot-based charging infrastructure, positioning electric trucks as customer-specific green logistics offerings, employing rigorous total cost of ownership analysis, building organizational capabilities through training, and engaging in policy advocacy. This research contributes actionable insights for logistics companies, policymakers, and industry stakeholders navigating the transition toward sustainable freight transportation in emerging markets.